Genetic and Functional Diversity of Pseudomonas aeruginosa Lipopolysaccharide - Lam, Joseph S.; Taylor, Véronique L.; Islam, Salim T.; Hao, Youai; Kocíncová, Dana (Frontiers in Microbiology, 2011)
Lipopolysccharide (LPS) is an integral component of the Pseudomonas aeruginosa cell envelope, occupying the outer leaflet of the outer membrane in this Gram-negative opportunistic pathogen. It is important for bacteria-host interactions and has been shown to be a major virulence factor for this organism. Structurally, P. aeruginosa LPS is composed of three domains, namely, lipid A, core oligosaccharide, and the distal O antigen (O-Ag). Most P. aeruginosa strains produce two distinct forms of O-Ag, one a homopolymer of D-rhamnose that is a common polysaccharide antigen (CPA, formerly termed A band), and the other a heteropolymer of three to five distinct (and often unique dideoxy) sugars in its repeat units, known as O-specific antigen (OSA, formerly termed B band). Compositional differences in the O units among the OSA from different strains form the basis of the International Antigenic Typing Scheme for classification via serotyping of different strains of P. aeruginosa. The focus of this review is to provide state-of-the-art knowledge on the genetic and resultant functional diversity of LPS produced by P. aeruginosa. The underlying factors contributing to this diversity will be thoroughly discussed and presented in the context of its contributions to host-pathogen interactions and the control/prevention of infection.